Bioremediation of Phenol in Synthetic Tobacco Industry Liquid Waste Using Pseudomonas Putida - Rahmi Yorika; Ismi Khairunnissa Ariani; Althofina Hawwa Hanifah (International Journal Labs, 2025)
Cigarette industry wastewater contains high phenol levels (100 mg/L), exceeding the regulatory limit of 0.5 mg/L (Minister of Environment Regulation No. 5/2014). Phenol is toxic, carcinogenic, and resistant to natural degradation, posing severe environmental and health risks. Existing treatments like ozonation (15.45% efficiency) and adsorption (60–80%) face limitations such as low efficiency and high operational costs. This research aimed to evaluate the bioremediation of synthetic tobacco wastewater using Pseudomonas putida, focusing on the effects of bacterial concentration (3–7%) and nutrient levels (0–2%) on phenol removal efficiency. A batch-culture experiment was conducted under controlled conditions (30°C, 150 rpm, 120 hours). Phenol concentration was measured via UV-Vis spectrophotometry, and bacterial growth was monitored using OD600. Data were analyzed using one-way ANOVA. The highest phenol removal (68%) occurred at 5% bacterial concentration and 2% nutrients, with OD600 = 1.000, indicating optimal bacterial growth. Nutrient variations did not significantly affect efficiency, but temperature fluctuations and carbon catabolite repression were identified as potential limiting factors. Pseudomonas putida offers a sustainable solution for phenol-laden wastewater, achieving near-compliance with regulatory standards. Future studies should optimize environmental controls and scale up the process for industrial applications.